A construção da identidade profissional do coordenador pedagógico e o assessoramento em formação permanente na escola: tecendo proposições - REGO, Leila Fernanda Mendes Everton (2021)
This research aimed to analyze the challenges faced by pedagogical coordinators who work in schoolswhen affirmingtheir professional identity as a permanent training advisor, with a goal of elaborating theoretical-methodological notes that help in the construction of work strategies and assist the pedagogic advising to teachers. In order to do so, we seek to answer the following questioning: how can the pedagogical coordinator plan, organize and execute work strategies consistent with their specificities and professional identity, establishing themselves as a permanent training advisorat public schools in the city of PaçodoLumiar - MA? To support the conceptual aspects of professional identity, we sought contributions from Nóvoa (1997), Santos (2011), Papi (2005), among others. Regarding the discussions of the pedagogical coordinator as a mobilizing figure in the training processes of teachers at schools, we refer to Imbernón (2011), Gouveia and Placco (2015), Domingues (2014), Libâneo (2018). From the above, we carried out a collaborative type of research, which was materialized with the use of research-action elements. As collaborators, we had a group of four pedagogical coordinators who work in stages from Early Childhood Education to the Final Years of Elementary School, using as data generation procedures: narrative memorial, pedagogical meetings and reflective sessions. The forms of systematization and interpretation of this research’s data indulged a reflective narrative. We found, with the support of these collaborators, that the performance of the pedagogical coordinator as a trainer in the schools from the municipal public education network of Paço do Lumiar - MA lacks an attentive and committed look from the departments that oversees their professional practice, among them, the Municipal Department of Education (SEMED). The research results indicate that, if the action of the pedagogical coordination in schools is to privilege, par excellence, the assistance in permanent training of teachers, it is healthy to think about permanent training for the trainer. In view of the findings, collaboratively, we proposed and systematized in a booklet some theoretical-methodological notes for the development of continuing education in network, among them: creation of a sector/department of continuing education in the education secretariats; construction of a collaborative training chain; organization of a continuous training agenda for the pedagogical coordinator; and a methodological itinerary for the development of continuing education for teachers under the management of the pedagogical coordinator.